Risk factors for synchronous or metachronous tumor development after endoscopic resection of gastric neoplasms - Lim, Joo Hyun; Kim, Sang Gyun; Choi, Jeongmin; Im, Jong Pil; Kim, Joo Sung; Jung, Hyun Chae (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2015)
Background Despite many advantages, the development of synchronous or metachronous neoplasm is one of the main concerns with endoscopic resection. We aimed to clarify the independent risk factors for synchronous or metachronous gastric neoplasm. Methods We retrospectively reviewed the medical records of all patients who had undergone endoscopic resection for gastric high-grade dysplasia or early gastric cancer between April 2001 and February 2011. Results Among 971 subjects, 56 synchronous neoplasms and 42 metachronous neoplasms developed during 12–131 months of follow-up. In univariate analysis, age over 65 years, male gender, absence of Helicobacter pylori infection, lower third location, mucosal atrophy, and intestinal metaplasia were related to multiple gastric neoplasms. In multivariate analysis, absence of H. pylori infection [odds ratio (OR) 1.610, 95 % confidence interval (CI) 1.038–2.497)], lower third location (OR 1.704, 95 % CI 1.070–2.713), and intestinal metaplasia (OR 4.461, 95 % CI 1.382–14.401) were independent risk factors for multiple gastric neoplasms. For synchronous neoplasm, primary tumor size less than 1 cm was the only independent risk factor. For metachronous neoplasm, absence of H. pylori infection (OR 2.416, 95 % CI 1.214–4.810) was found to be the only independent risk factor. H. pylori eradication was found to be unrelated to the development of metachronous gastric neoplasms. Conclusions For tumors located in the antrum and accompanied by intestinal metaplasia, meticulous endoscopic evaluation with close follow-up after endoscopic resection is recommended.